DIFFICULTIES IN TEACHING PRONUNCIATION - Xurramov Rashid Mamayusufovich ("Conference on Universal Science Research 2023", 2023)
This article discusses the concept of pronunciation, the meaning of pronunciation and its importance in learning foreign languages.